BENEFITS OF FLASHCARD MEDIA IN SPEAKING SKILLS OF STUDENTS WITH SPECIFIC LEARNING DIFFICULTIES - Intan Sari Ramdhani (Jurnal Visi Ilmu Pendidikan, 2022)
Speaking skills are one of the language skills that must be mastered by students, including elementary school (SD) students. This skill must always be honed, especially by elementary school students who have specific learning difficulties, so that students can play an active role in communicating. Therefore, it is necessary to have good stimulation to improve the speaking skills of elementary school students. Flashcard media can be used as a medium to improve students' speaking skills. The method used in this research is a literature review or literature study. The results of this study indicate that the flashcard medium is practical and effective when used in learning. By utilizing Flash Card media, learning is more conducive and fun because Flashcard media can attract students' attention. Students' mastery of language develops and students' speaking skills, especially those of students with specific learning disabilities, increase. Students are easier to add and pronounce vocabulary and memorize vocabulary, which helps students recognize letters and make it easier for students to be able to tell stories according to what is in the picture, so that students' imaginations develop, helping students to learn to think critically, students' enthusiasm for learning increases, and students become more courageous.